Poems for 7 Year Olds - A. F. Harrold (Macmillan Children's Books, 2022)
fairy tales, food, friends, school and ghosts. Includes classic and contemporary poems by Lewis Carroll, A.F. Harrold, Matt Goodfellow, Charles Causley, Laura Mucha, Jan Dean, Kate Wakeling, Sabrina Mahfouz, Paul Cookson, Brian Moses, John Siddique and many more.
Keywords: Poetry Section -- Poetry Section